Given 12−(−2) over a line 12−6÷2
We can use PEMDAS rule and solve the expression in the order as given below:-
1. Parentheses
2. Exponents
3. Multiplication
4. Division
5. Addition
6. Subtraction
Now solving for given expression:-
![\frac{12-(-2)}{12-(\frac{6}{2})}\\\\=\frac{12+2}{12-3}\\\\=\frac{14}{9}](https://tex.z-dn.net/?f=%20%5Cfrac%7B12-%28-2%29%7D%7B12-%28%5Cfrac%7B6%7D%7B2%7D%29%7D%5C%5C%5C%5C%3D%5Cfrac%7B12%2B2%7D%7B12-3%7D%5C%5C%5C%5C%3D%5Cfrac%7B14%7D%7B9%7D)
So final answer is 14/9 i.e. 14 over 9.
Answer:
D
Step-by-step explanation:
(5·5)*x = 25*x =25^x
the rest are wrong
Answer:
80%
Step-by-step explanation:
Answer:
Step-by-step explanation:
as given in question that a > 0 so
if we put a=1
we get g(x) = f(x)
now put a =2
we get
g(x) = 2 f(x)
here we can see that g(x) would always be greater than or equals to f(x)
so we can say that the graph of g(x) will never be narrower than graph of g(x)
Answer:
try
Step-by-step explanation:
try solving it on ur own or take a educated guess